Local Delivery Of Irinotecan To Recurrent Glioblastoma At Reoperation Offers A Safe Therapeutic Advantage Over Systemic Delivery. (31st January 2018) - Cruickshank, Garth; Ngoga, Desire; Detta, Allah; Lewis, Andy; Holden, Rebecca; Fayaye, Olufawe
Abstract: Direct drug delivery to a brain tumours offers the surety of access, together with the potential to realise at least therapeutic concentrations. With previously used systemic drugs toxicity and removal mechanisms are avoided. With new formulations drug activation and duration can be explored for low local toxicity, and tumour impact with sequential imaging. In this early study Irinotecan a drug with known efficacy against glioma but with limiting systemic toxicity has been incorporated into biodegradeable hydrogel microspheres and injected into the post-surgical cavity wall in patients with recurrent glioblastoma. 10 patients with focally recurrent GBM were recruited with 9 undergoing injection with up to 3mls of microbeads in alginate suspension in up to 60 ~ 8mm injection tracks after surgical resection (100mg). Patients were assessed for immediate (72hrs) toxicity with clinical assessment and imaging. Pharmacokinetic determination of Irinotecan and SN 38 active metabolite allowed confirmation of activation and comparator with known plasma toxicity profiles. Follow-up was planned for a minimum of 6/12 for SAE but continued to allow overall survival estimation. No overt SAE were determined for this group of patients with imaging and steroid use indicating less local swelling and wound healing issues than have been demonstrated for Carmustine wafers despite early offloading. Phamacokinetic measures (SN38 plasma curves) indicate a much higher activation of Irinotecan (>90%) than expected but shorter period of exposure. Survival curves suggest clinical benefit with 4/9 patient living longer than 8 months warranting further exploration of this safe approach